2017
DOI: 10.1186/s13071-017-2151-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tick-borne haemoparasites in small ruminants in Turkey and diagnostic sensitivity of single-PCR and RLB

Abstract: BackgroundTick-borne haemoparasitic diseases (TBHDs), caused by Theileria, Babesia, Anaplasma and Ehrlichia, are common in regions of the world where the distributions of host, pathogen and vector overlap. Many of these diseases threaten livestock production and some also represent a concern to human public health. The primary aim of this study was to determine the prevalence of the above-mentioned pathogens in a large number of blood samples (n = 1979) collected from sheep (n = 1727) and goats (n = 252) in Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 62 publications
5
56
1
Order By: Relevance
“…Results demonstrated that PCR was more sensitive than the RLB assay. This is in agreement to previous observations [29,45]. It is well established that the sensitivity and specifi city of any PCR assay is affected by so many factors, like primers and other ingredients used during the amplifi cation phase of target DNA [46].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Results demonstrated that PCR was more sensitive than the RLB assay. This is in agreement to previous observations [29,45]. It is well established that the sensitivity and specifi city of any PCR assay is affected by so many factors, like primers and other ingredients used during the amplifi cation phase of target DNA [46].…”
Section: Discussionsupporting
confidence: 92%
“…However, the relatively high kappa agreement (κ = 0.74) between the two tests suggests that RLB assay should still be considered a reliable assay in diagnosing Babesia spp. especially in possible cases of mixed infections [21,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ticks generate indirect damage due to their key role in the transmission of a large number of infectious agents [44]. As mentioned in Bilgic et al [48], in recent decades, the socioeconomic impact of small ruminants has grown worldwide, and therefore more attention is now being given to the pathogens that affect sheep and goats. As in the case of bovines, the main tick-borne diseases are babesiosis, anaplasmosis, theileriosis and heartwater [3].…”
Section: Economic and Health Impact Of The Ticks In Small Ruminants 3mentioning
confidence: 99%
“…As in the case of bovines, the main tick-borne diseases are babesiosis, anaplasmosis, theileriosis and heartwater [3]. Losses attributed to these diseases include mortality, production losses, diagnostic, veterinary treatment and control costs of ticks [48]. In China, it is estimated that Anaplasma, Babesia and Theileria species infect about 35 million of small ruminants.…”
Section: Economic and Health Impact Of The Ticks In Small Ruminants 3mentioning
confidence: 99%